Entropy-based intra-coding RDO estimation for HEVC; The 9th International Forum on on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Sharabayko M. P. Maksim Pavlovich (2014, 2014)
Title screen